2017
DOI: 10.35800/jjs.v8i1.15330
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor Yang Mempengaruhi Penyerapan Anggaran Pendapatan Dan Belanja Daerah (Apbd) Pemerintah Kabupaten Kepulauan Talaud

Abstract: Abstract. Budget is a statement regarding the estimation of the performance to be achieved during a certain period of time stated in the financial measures and expressed how much it costs to the plans made (expenses / expenditures) as well as how much and how to get money to fund the plan. Budget (APBD) is the annual local government financial policy which is based on statutory provisions in force, a number of considerations for the formulation, monitoring, control and evaluation is done. Absorption of budget … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 3 publications
4
10
0
6
Order By: Relevance
“…The results of this study further strengthen the importance of continuing to improve the competence of human resources owned by the work unit, especially those related to the budget, such as budget compilers, commitment-making officials, procurement committees, treasurers, and others, this confirms several previous studies [6,7].…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study further strengthen the importance of continuing to improve the competence of human resources owned by the work unit, especially those related to the budget, such as budget compilers, commitment-making officials, procurement committees, treasurers, and others, this confirms several previous studies [6,7].…”
Section: Discussionsupporting
confidence: 89%
“…So that in using the budget effectively, efficiently, and economically, budget absorption will be fast and evenly absorbed until the end of the year. The study results (Gagola et al, 2017;Syakhrial, 2018;Ramadhani & Setiawan, 2019) found that the procurement of goods/services had a positive and significant effect on budget absorption. However, Puluala (2021) found that the procurement of goods/services had a positive and insignificant impact on budget absorption.…”
Section: Introductionmentioning
confidence: 92%
“…Planning is an essential element in the organization. Planning determines all activities that need and will be carried out to achieve the goals and objectives to be completed (Gagola et al, 2017). To realize the plan, a budget is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Senada dengan hal tersebut, Ruwaida et al (2016) juga menemukan bahwa faktor SDM, pengadaan barang dan jasa dan koordinasi memberikan kontribusi lebih dari 10 persen terhadap penyerapan anggaran belanja pendidikan di Provinsi Aceh. Mendukung hasil penelitian tersebut, Gagola et al (2017) KPPN Jakarta II. Faktor-faktor strategis internal dan eksternal sangat menentukan bagaimana desain strategi optimalisasi tingkat penyerapan anggaran. Strategi merupakan berbagai cara untuk mencapai tujuan (Solihin, 2012).…”
Section: Pendahuluanunclassified